Characterization of a phenol-degrading bacterium isolated from an industrial effluent and its potential application for bioremediation - Paisio, Cintia Elizabeth (2012)
The use of native microorganisms is a useful strategy for phenol bioremediation. In the present work, a bacterial strain, named RTE1.4, was isolated from effluents of a chemical industry. The strain was able to grow at high concentrations of phenol and its derivatives, such as guaiacol, 2,4-dichlorophenol and pentachlorophenol, as well as in a medium containing industrial effluents. This bacterium was identified as Acinetobacter sp. using morphological, physiological, biochemical and 16S rRNA gene analysis. Acinetobacter sp. RTE1.4 degraded phenol (200 to 600 mg/L) at wide pH range and temperature (5-9 and 25-37°C, respectively) demonstrating high adaptation ability to different conditions. The strain would metabolize phenol by the ortho-pathway since catechol 1,2-dioxygenase activity was detected. When bacteria were grown in medium containing phenol, an altered whole-cell protein pattern was observed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), with the lack of some low-molecular mass polypeptides and an increase in the relative abundance of high-molecular mass proteins after treatment. Considering that the use of native strains in bioremediation studies shows several ecological advantages and that the studied bacterium showed high tolerance and biodegradation capabilities, Acinetobacter sp. RTE1.4 could be an appropriate microorganism for improving bioremediation and biotreatment of areas polluted with phenol and/or some of its derivatives. Moreover, the establishment of the optimal growth conditions (pH, temperature, concentration of the pollutant) would provide baseline data for bulk production of the strain and its use in bioremediation processes. © 2013 Copyright Taylor and Francis Group, LLC.